2023
DOI: 10.1371/journal.pone.0280441
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ preferences in dental care: A discrete-choice experiment and an analysis of willingness-to-pay

Abstract: Introduction Dental diseases are a major problem worldwide. Costs are a burden on healthcare systems and patients. Missed treatments can have health and financial consequences. Compared to other health services, dental treatments are only covered in parts by statutory health insurance (SHI). Using the example of dental crowns for a cost-intensive treatment, our study aims to investigate whether (1) certain treatment attributes determine patients’ treatment choice, and (2) out-of-pocket payments represent a bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…The factors most frequently identified in studies are out-of-pocket payment, dental fear, aesthetics, and pain. Out-of-pocket payment can be considered a decisive factor of choice, as recently shown in willingness-to-pay studies of different countries, e.g., Japan [167], England [88], and Germany [168]. The UK, Saudi Arabia, the USA, India, Brazil, Turkey, Germany, and Canada are the countries with most identified articles (n>=8 articles), with out-of-pocket payment as most frequently mentioned factor of choice.…”
Section: Discussionmentioning
confidence: 98%
“…The factors most frequently identified in studies are out-of-pocket payment, dental fear, aesthetics, and pain. Out-of-pocket payment can be considered a decisive factor of choice, as recently shown in willingness-to-pay studies of different countries, e.g., Japan [167], England [88], and Germany [168]. The UK, Saudi Arabia, the USA, India, Brazil, Turkey, Germany, and Canada are the countries with most identified articles (n>=8 articles), with out-of-pocket payment as most frequently mentioned factor of choice.…”
Section: Discussionmentioning
confidence: 98%
“…Cosmetic dental procedures can help to reduce these stigmata and the associated psychological distress (Matsuyama et al, 2021). A discrete choice experiment found that aesthetic treatments were crucial for participants choice of dental treatment (Felgner & Henschke, 2023). Yet, cosmetic treatments are largely excluded from coverage in most European countries (Winkelmann et al, 2023;Winkelmann, Gómez Rossi, & van Ginneken, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Araştırma yaş ve cinsiyetin WTP'yi etkilediği ve bireylerin cepten ödeme yapmaktansa sigortanın karşıladığı standart tedaviyi tercih ettikleri tespit edilmiştir. 38…”
Section: Discussionunclassified